(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The initial capital of Andhra was Srikakulam (modern Srivakulam) and the later capital wasDhanyakataka (Dharnikot or Amaravati). Both the places were on the banks of river Krishna. The conceptof life outlook and free environment found in Indian literature is also supported by the illustrations of art,which is a remarkable fact.Not only in Indian but also in foreign art, flying figures have been marked inabundance in various other sculptures